1. выражения а)(x-2)(x+3) б)(2x^{2}-y^{2})(3y^{2}-x^{2}) 2.разложите на множители a)ха + xb + 6 a +6 b б)x ^{3} - x^{2}+x -1 в)ab-2a-2b +4 3. и вычислите при х=-3 2-(x-1)(x+1)

2006veronika34 2006veronika34    3   07.03.2019 19:50    2

Ответы
Tittans16 Tittans16  24.05.2020 03:57

файл

===========================


1. выражения а)(x-2)(x+3) б)(2x^{2}-y^{2})(3y^{2}-x^{2}) 2.разложите на множители a)ха + xb + 6 a +6
ПОКАЗАТЬ ОТВЕТЫ
2508sanya 2508sanya  24.05.2020 03:57

(x-2)(x+3)=x^2+3x-2x-6=x^2+x-6

(2x^2-y^2)(3y^2-x^2)=7x^2y^2-2x^4-3y^4

 

xa+xb+6a+6b=x(a+b)+6(a+b)=(a+b)(x+6)

x^3-x^2+x-1=(x^3-1)-(x^2-x)=(x-1)(x^2+x+1)-x(x-1)=(x-1)(x^2+x+1-x)=(x-1)(x^2+1)

 

2-(x-1)(x+1)=2-(x^2-1)=2-x^2+1=3-x^2.   x=3   3-3^2=3-9=-6 

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра